Limits of Meritocracy. How Fields of Study and Gender Segregation Affect Social Stratification in Finland - Prix, Irene (My University, 2014)
This dissertation critically reviews the idea of meritocracy from both a theoretical and an empirical perspective. Based on a discussion of classical texts of social philosophy and sociology, it is argued that meritocracy as a concept for social stratification is best compatible with the sociological tradition of status attainment research: both frame social inequality in primarily individualistic terms, centring on the role of ascribed (e.g., gender, social background) and achieved (e.g., educational qualifications) characteristics for determining individuals’ socioeconomic rewards. This theoretical argument introduces the research problem at the core of this dissertation: to what extent can the individualistic conception of social stratification be maintained empirically? Fields of study and their interaction with educational attainment levels play a prominent role in the analysis of this question. Drawing on sociological versions of segmented labour market theory, it is assumed that fields of study may channel individuals into heterogeneous political-economic contexts on the labour market, which potentially modify the socioeconomic benefit individuals derive from their qualification levels. The focus on fields of study may also highlight economic differentials between men and women that derive from the persisting segregation of men’s and women’s occupational and educational specializations rather than direct gender discrimination on the labour market. The quantitative analyses in this dissertation consist of three research articles, which are based primarily on Finnish data, but occasionally extend the view to other European countries. The data sources include register-based macro- and microdata as well as survey data. Article I examines the extent and the patterns of gender segregation within the Finnish educational system between 1981 and 2005. The results show that differences between men’s and women’s field specializations have for the most part remained stable during this period, with particularly high levels of gender segregation observed at lower educational levels. The focus in Article II rests on the effects of gender-segregated fields of study on higher education graduates’ occupational status. It is shown that fields of study matter for accessing professional jobs and avoiding low-skilled positions in Finland: at the early career stage, particularly polytechnic graduates from female-dominated fields are less likely to work in professional positions. Finnish university graduates from male-dominated fields were more likely than their peers with different specializations to work as professionals, yet they also faced a greater risk of being sorted into lowskilled jobs if they failed to make use of this advantage. Article III proceeded to analyse the joint impact of educational qualification levels and fields of study on young adults’ median earnings in Finland between 1985 and 2005. The results show that qualification levels do not confer a consistent benefit in the process of earnings stratification. Advanced qualifications raise median earnings most clearly among individuals specializing in the same field of study. When comparing individuals with different field specializations, on the other hand, higher-level qualifications do not necessarily lead to higher median earnings. Overall, the findings of this dissertation reveal a heterogeneous effect of education for achieving social positions, which challenges individual-centred, meritocratic accounts of social stratification and underlines the problematic lack of structural and institutional dimensions in the dominant account of social status attainment.

Tämä väitöskirja tarkastelee kriittisesti meritokratian ideaa yhteydessä yhteiskunnan kerrostumarakenteeseen sekä teoreettisesta että empiirisestä näkökulmasta. Yhteiskuntafilosofian ja sosiologian klassikoiden tarkastelun kautta käy ilmi, että meritokratia sosiaalista kerrostumista jäsentävänä periaatteena on yhteensopiva lähinnä sosiologisen “status attainment”-tutkimusperinteen kanssa: molemmat käsittelevät yhteiskunnallista eriarvoisuutta pelkästään yksilöiden ominaisuuksien kautta, painottamalla henkilöiden taustamuuttujia (esim. perhetausta, sukupuoli) ja koulutussaavutuksia. Teoreettinen keskustelu johdattaa väitöskirjan keskeiseen tutkimusongelmaan: missä määrin individualistinen käsite yhteiskunnallisesta kerrostumisesta kestää empiirisen tarkastelun? Tähän kysymykseen haetaan vastausta analysoimalla koulutusalan ja tutkintotason välistä vuorovaikutusta kerrostumisprosessissa. Sosiologiset työmarkkinoiden segmentaatio-teoriat antavat olettaa, että koulutusala kanavoi ihmiset erilaisiin poliittis-taloudellisiin konteksteihin työmarkkinoilla, mikä vaikuttaa tutkintojen mahdollistamiin tuloihin ja ammattiasemiin. Painottamalla koulutusalan merkitystä tämä väitöskirja tuo esiin sellaisia sukupuolivaikutuksia työmarkkinoilla, jotka johtuvat naisten ja miesten erikoistumisesta eri koulutusaloille pikemmin kuin esimerkiksi sukupuoleen perustuvasta syrjinnästä työmarkkinoilla. Väitöskirjan kvantitatiiviset analyysit on esitetty kolmessa artikkelissa, jotka perustuvat lähinnä Suomea koskeviin aineistoihin, mutta mukana on myös muuta Eurooppaa koskevaa dataa. Lähdeaineistoina käytetään sekä rekistereihin että kyselytutkimuksiin pohjautuvaa dataa. Ensimmäisessä artikkelissa tarkastellaan miesten ja naisten eriytymistä eri koulutusaloille suomalaisessa koulutusjärjestelmässä vuodesta 1981 vuoteen 2005. Tulokset osoittavat että sukupuolten välinen eriytyminen on pysynyt melko vakaana, erityisesti alemmilla koulutustasoilla. Toisessa artikkelissa tutkitaan miten sukupuolittuneet koulutusalat vaikuttavat ammattikorkeakouluista ja yliopistoista valmistuneiden ammatilliseen asemaan uran alkuvaiheessa. Tulosten mukaan koulutusalan naisvaltaisuus heikentää ammattikorkeakouluista valmistuneiden todennäköisyyttä työskennellä erityisasiantuntijoina. Yliopistotutkinto miesvaltaiselta alalta lisää erityisasiantuntijatyön todennäköisyyttä, mutta uralla etenemisen epäonnistuessa, riski ajautua vain vähän ammattitaitoa vaativaan työhön kasvaa verrattuna naisvaltaiselta alalta valmistuneisiin. Kolmas artikkeli käsittelee koulutusalojen ja tutkintotason yhteisvaikutusta nuorten aikuisten mediaanituloihin Suomessa vuosina 1985, 1995 ja 2005. Alojen sisäisissä vertailuissa tulot kasvavat koulutustason noustessa, mutta alojen välisissä vertailuissa korkeampi koulutustaso ei välttämättä tuo korkeampia mediaanituloja. Yhteenvetona voidaan todeta, että tutkintotasolla ei ole yhtenevää vaikutusta sosiaalisen aseman saavuttamisessa Suomalaisessa yhteiskunnassa. Tulos haastaa yksilökeskeiset, meritokraattiset tulkinnat sosiaalisesta kerrostumisprosessista ja korostaa rakenteellisten ja institutionaalisten ulottuvuuksien puutetta vallitsevissa käsityksissä sosiaalisen aseman saavuttamisesta.